REPRESENTASI PSIKOLOGI PEREMPUAN AKIBAT BUDAYA PATRIARKI DALAM CERPEN “PEREMPUAN ITU PERNAH CANTIK” KARYA MASHDAR ZAIDAL - Pasaribu, Christin; Firmansyah, Dodi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Literary works are fictional writings that describe the reality of people's lives. In writing a work, the author expresses his thoughts based on experiences in society. The literary work in the form of a short story entitled "Perempuan Itu Pernah Cantik" by Mashdar Zaidal, which was studied using a literary sociology approach and descriptive qualitative methods, is very relevant to the mental impact of patriarchal culture on women in the real world. This short story describes the mental image of women due to the impact of patriarchal culture after marriage. Women before and after marriage have very different differences, starting from their physical appearance, level of self-confidence, and time for themselves because they are busy taking care of household work which is often ignored by their husbands. Patriarchal culture in Indonesia is clearly illustrated in the short story "Women Were Ever Beautiful" which slowly damages women's mental health, starting from lack of self-confidence, unstable emotions, feeling excessively anxious and so on.